Optimizing Your Modernization Journey with AWS - Grandhi, Mridula (Packt Publishing, Limited, 2023)
Cover – Title Page – Copyright and Credits – Dedications – Contributors – Table of Contents – Part 1: Migrating to the Cloud – Chapter 1: Introduction to Cloud Transformation – Introduction to the cloud – The origins of cloud computing – Key characteristics of cloud computing – On-demand self-service – Wide range of network access – Multi-tenant model and resource pooling – Rapid elasticity – PAYG model – Measured service and reporting – Understanding the motivators for cloud adoption – Resilience – Advanced security – Carbon footprint reduction – Improved optimization and efficiency – Faster innovation and business agility – Understanding CSPs – Amazon Web Services (AWS) – Microsoft Azure – Google Cloud Platform – Alibaba Cloud – Exploring the service models - SaaS, PaaS, and IaaS – Infrastructure as a Service (IaaS) – Platform as a Service (PaaS) – Software as a service (SaaS) – Exploring the deployment models - public, private, hybrid, multi, and community – The public cloud – The private cloud – The hybrid cloud – Multi-cloud – The community cloud – Comparison between the different cloud deployment models – Summary – Further reading – Chapter 2: Understanding Cloud Migration – Cloud migration - key concepts and fundamentals – What is cloud migration? – AWS cloud fundamentals – Understanding the key cloud migration challenges – Lack of enterprise-wide vision – Lack of cloud-first mindset – Lack of technical skill sets – Lack of a well-defined strategy – Lack of data security and risk assessment – Lack of accurate migration budget assessment – Lack of on-premises-to-cloud compatibility – The evolving benefits of cloud migration – Building a cloud-first mindset – Assess - understanding the present – Vision - imagining the future state – Mission - setting the goals.
Description based on publisher supplied metadata and other sources
Keywords: Amazon Web Services (Firm); Cloud computing; Web services; Electronic books